Evaluation of User’s Satisfaction with Reference Services in Selected Federal University Libraries in Southeastern Nigeria - Otonekwu Florence Onyeisi; Saliu Usman Ajisafe; Oyedokun Tunde Toyese (Insaniyat : Journal of Islam and Humanities, 2019)
The study evaluated users’ satisfaction with the reference services of federal university libraries in southeastern Nigeria. The study adopted a descriptive survey design, and questionnaire served as an instrument for data collection. Drawing from a population of 20,570, a questionnaire was administered to 394 undergraduate library users of which 351 were completed and found useful for data analysis. The findings revealed that users were satisfied with library reference services except those they are not familiar with and none of the categories of reference services was rated very high. Most library users are not familiar with translation service, internet service, and e-mail service along with library OPAC. Reference librarians have a good customer relationship with the users, even though they are yet to fortify their presence in an online environment. Sequential to the above unearthing, recommendations were given that reference librarians should adopt public relation technique in relating to users and other stakeholders of the library. More so, awareness of reference services should be created through library publicity and marketing of library services among the community of users. The recommendation was also given that the reference librarian should be ICT compliance to be able to perform excellently in an online environment.